Impact of Short-Term Training Camp on Aortic Blood Pressure in Collegiate Endurance Runners - Tomoto, Tsubasa; Sugawara, Jun; Hirasawa, Ai; Imai, Tomoko; Maeda, Seiji; Ogoh, Shigehiko (Frontiers in Physiology, 2018)
To investigate the influence of short-term vigorous endurance training on aortic blood pressure (BP), pulse wave analysis was performed in 36 highly trained elite collegiate endurance runners before and after a seven-day intense training camp. Subjects participated three training sessions per day, which mainly consisted of long distance running and sprint training to reach the daily target distance of 26 km. After the camp, they were divided into two groups based on whether the target training was achieved. Aortic systolic BP, pulse pressure, and tension-time index (TTI, a surrogate index of the myocardial oxygen demand) were significantly elevated after the camp in the accomplished group but not in the unaccomplished group, whereas the brachial BP remained unchanged in both groups. The average daily training distance was significantly correlated with the changes in aortic systolic BP (r=0.608, p=0.0002), pulse pressure (r=0.415. p=0.016), and TTI (r=0.438, p=0.011). These results suggest that aortic BP is affected by a short-term vigorous training camp even in highly trained elite endurance athletes presumably due to a greater training volume compared to usual.